Soil Testing to Predict Dissolved Reactive Phosphorus Loss in Surface Runoff from Organic Soils. Issue 5 (29th August 2014) - Zheng, Z.M.; Zhang, T.Q.; Wen, G.; Kessel, C.; Tan, C.S.; O'Halloran, I.P.; Reid, D. K.; Nemeth, D.; Speranzini, D.
Abstract : Phosphorus loss from surface runoff contributes to eutrophication of surface water, a problem that is often severe from polders with organic soils where agricultural production is intensive. A soil P test is essential to predict the potential for P losses to precisely conduct environmental risk assessment and to efficiently develop and evaluate beneficial management practices. This study evaluated the possibility of using the environmental and agronomic soil P tests, soil P sorption index (PSI), and degree of soil P saturation (DPS), which are used for mineral soils, to predict surface runoff dissolved reactive P (DRP) from organic soils. Forty‐four soils from eight subgroups representative of organic lands across Ontario were selected to provide a wide range of soil test P (STP) within each category. A surface runoff study was conducted following the U.S. National Phosphorus Research Project protocol. Flow‐weighted mean runoff DRP concentration (DRP30 ) was linearly related to soil water‐ and CaCl2 –extractable P concentrations but with data distribution patterns that inefficiently represented the soil variability in P release potentials. The runoff DRP30 was significantly related to Bray‐1 P and FeO‐extractable P concentrations in split‐line models, each with a change point, but not to Mehlich‐3 P and Olsen P. All DPS values calculated based on STP and their derived PSIs were closely related to runoff DRP30 in either a linear or a split‐line model. The DPS values expressed as Bray‐1 P/(PSI + Bray‐1 P) and FeO P/(PSI + FeO P) showed the highest correlation with runoff DRP30 and thus can be recommended as environmental risk indicators of surface runoff DRP from organic soils.